"Helping" Versus "Being a Helper": Invoking the Self to Increase Helping in Young Children. Issue 5 (29th April 2014) - Bryan, Christopher J.; Master, Allison; Walton, Gregory M.
<x xml:space="preserve">Abstract</x> Can a subtle linguistic cue that invokes the self motivate children to help? In two experiments, 3‐ to 6‐year‐old children (N = 149) were exposed to the idea of "being a helper" (noun condition) or "helping" (verb condition). Noun wording fosters the perception that a behavior reflects an identity—the kind of person one is. Both when children interacted with an adult who referenced "being a helper" or "helping" () and with a new adult (), children in the noun condition helped significantly more across four tasks than children in the verb condition or a baseline control condition. The results demonstrate that children are motivated to pursue a positive identity. Moreover, this motivation can be leveraged to encourage prosocial behavior.